Odpisy aktualizujące wartość zapasu produktów gotowych jako bilansowy wyraz pomiaru i prezentacji ryzyka działalności gospodarczej - Szydełko, Alfred (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Risky situations are connected with even' enterprise. The specification of producers caused that we have a risky situation with cost of product manufacturing and the depreciation of products inventory. In Polish and international accounting law there are different aspects which are connected with the depreciation of products inventory, measurement, bookkeeping and the presentation in financial statement valuation allowance. These procedures can be used in enterprise risk management. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 427-433